Factores que inciden en la deserción académica de los estudiantes de la carrera de Comunicación de la Universidad Técnica de Babahoyo - Solano Bravo, Mayerlin Sthefany (2020)
Attrition refers to the abandonment of studies by the student and is one of the problems they face in education, because the fact that students interrupt their educational training is worrisome, since this impacts their lives in The present and future. Thus, academic dropout is influenced by several factors including family, economic, migratory, health, emotional, which increase the student risk towards abandonment of their studies. In our work, each of these factors will be analyzed and each one of these will be developed descriptively, making reflections on this problem. The family implies a fundamental factor in the educational formation of young people, since it is the medium where they interact and develop, since their life and academic success depend on it. This is coupled with migration and the economy of the family, since family disintegration or lack of financial resources significantly impairs student stability. In turn, the affectivity of the context marks an important place in the student, since the good or bad relationships they have in the university and society depend on it.